Synthesis of diblock functional poly(ɛ-caprolactone) amphiphilic copolymers grafted with bioactive molecules and characterization of their micelles - Huang, Yi-Ting; Peng, Kang-Yu; Chiu, Fang-Chyou; Lee, Ren-Shen (Polymer journal, 2013)
In this study, the grafting of an alkynyl bioactive compound to poly(α-azo-ɛ-caprolactone)- b -poly(ɛ-caprolactone) (PαN 3 CL- b -PCL) was performed using Huisgen’s 1,3-dipolar cycloaddition, also known as click chemistry. The grafted copolymers were successfully obtained at various ratios, as confirmed by nuclear magnetic resonance, gel permeation chromatography and Fourier transform infrared spectroscopy. The graft-block poly(α-azo- ɛ -caprolactone- graft -bioactive molecule) ((PαN 3 CL- g -BioM)- b -PCL) copolymers were semicrystalline, with the melting temperature ( T m ) depending on the type and the amount of grafting compounds. Grafting of 1-dimethylamino-2-propyne, pent-4-ynyl nicotinate and propargyl N -benzyloxycarbonyl-4-hydroxy prolinate onto the P α N 3 CL- b -PCL caused these amphiphilic copolymers to self-assemble into micelles in the aqueous phase. The critical micelle concentration (CMC) ranged from 4.6 to 20 mg l −1 , and the average micelle size ranged from 105 to 162 nm. The hydrophilicity and the unit of the grafting compounds influenced the stability of the micelle. This study describes the drug-entrapment efficiency and drug-loading content of the micelles, which were dependent on the composition of the graft-block polymers. The results from in vitro cell viability assays showed that (PαN 3 CL- g -BioM)- b -PCL possessed low cytotoxicity. Diblock functional poly(ɛ-caprolactone)s (PαN 3 CL- g -BioM)- b -PCLs grafted with bioactive molecules were performed by Huisgen’s 1,3-dipolar cycloaddition. These amphiphilic copolymers can self-assemble into micelles in the aqueous medium with critical micelle concentration (CMC) in the range 4.6–20 mg l −1 , and the average micelle size ranged from 105 to 162 nm. In vitro cell viability assays showed that (PαN 3 CL- g -BioM)- b -PCL has low cytotoxicity.